Speech therapy and orthognathic surgery: a literature review - Milane França Neves Silva; Laura Davison Mangilli Toni (Revista Brasileira de Cirurgia Plástica)
Introduction: Dentofacial deformities are associated with changes in dental occlusion, which may cause changes in the myofunctional system according to the type of disproportion. These deformities can cause changes and/or adaptations in the stomatognathic system. The objective of this study was to identify the relationship between speech therapy and orthognathic surgery based on refereed publications. Method: A bibliographic survey was conducted without considering a specific publication period in the databases, PubMed, SciELO and BVS. Results: Fifteen articles were critically evaluated with respect to the type of study, objectives, number and sex of participants, methodology, results and conclusions. Based on their aims, the articles were grouped into 1) speech-therapy group (STG); 2) changes group (CG); 3) techniques group (GT) and 4) others group (OG). Conclusion: There is little information regarding direct speech therapy intervention, and the majority of the studies were directed to the aesthetic and functional changes in the hard and soft tissue in patients who underwent orthognathic surgery. Some studies addressed methods and/or specific examination procedures to verify the changes in the soft and hard tissues of the facial profile of patients who underwent orthognathic surgery, and a study detailed the profile of individuals who underwent treatment for dentofacial deformity and apnea-hypopnea syndrome.